Persistent obstacles for return to work after COVID-19 infection – an explorative follow-up study in Sweden - Öhlén, Hilda; Santos Tavares Silva, Iolanda; Gustafsson, Marie; Jarl, Sara; Björkdahl, Ann (Frontiers in Rehabilitation Sciences, 2025)
Design, aim and methodTo explore in patients with postcovid-19 condition the influence of various factors on return to work in the year following diagnosis. The study had an explorative quantitative and qualitative design based on interviews with 41 hospitalized (HC) and 63 primary care (PC) COVID-19 patients. RTW was described at 3 and 12 months, and differences between groups, changes over time and possible factors explaining RTW were analysed statistically. Qualitative analyses with content analysis of interviews were performed to describe obstacles to work.ResultThe obstacles for RTW were persistent symptoms such as fatigue, cognitive dysfunction and breathlessness with the consequences for work as lack of energy, decreased physical capability, decreased mental stamina, reduced cognitive ability, increased sensitivity to stress and general reduced capacity. At 12 months, 50% and 70% of patients in the PC and HC groups, respectively, had returned to full-time work, while 20% of patients in both groups had not RTW at all. To function at work, many patients expressed that they required adaptations. RTW was not dependent on the initial severity of COVID-19 or type of work. The likelihood of RTW was higher in males with COVID-19 onset during the second wave.ConclusionRTW may be limited after COVID-19 infection, regardless of its initial severity. Women with persistent covid had greater difficulty than men in returning to work. Limitations were due to a general reduced capacity mainly caused by physical and mental fatigue, and cognitive dysfunction. However, the support from employers and the environment also has an impact on the RTW. If necessary, appropriate rehabilitation measures should be offered and adaptations of work content and the organization of the work at the workplace are of great importance.